Different clinical features between patients with ROS1-positive and ALK-positive advanced non-small cell lung cancer. Issue 2 (February 2021) - Ji, Xianxiu; Xie, Huikang; Zhu, Ren; Chen, Bin; Jiang, Sen; Luo, Jie
Objective: To compare the baseline clinical characteristics between patients with ROS1 -positive and ALK -positive advanced non-small cell lung cancer (NSCLC), and the correlations of these subtypes with the distribution of metastases. Methods: We compared the clinical characteristics and imaging features of patients with ROS1 -positive and ALK -positive NSCLC using statistical methods. Results: Data for 232 patients were analyzed. Compared with ALK -positive NSCLC, ROS1 -positive NSCLC was more likely to occur in women (71% vs 53%), and primary lesions ≤3 cm were more common in patients with ROS1 -positive compared with ALK -positive NSCLC (58% vs 37%). There was no significant difference in the distribution of metastases between the two groups. Subgroup analysis within the ROS1 -positive group showed that, compared with primary lesions >3 cm, primary lesions ≤3 cm were more likely to present as peripheral tumors (72% vs 43%) and more likely to exhibit non-solid density (44% vs 4%). Conclusions: Although ROS1 -positive and ALK -positive NSCLCs show similar clinical features, the differences may help clinicians to identify patients requiring further genotyping at initial diagnosis.